Innovative Technologies for Improved Water Productivity and Climate Change Mitigation, Adaptation, and Resilience: A Review - E. Oiganji; H. Igbadun; P. S. Amaza; R. Z. Lenka (Journal of Applied Sciences and Environmental Management)
Water scarcity, exacerbated by climate change, poses severe challenges to agriculture, food security, and sustainable development, particularly in vulnerable regions. This study examines innovative technologies for improving water productivity and mitigating the impacts of climate change. Key technologies discussed include precision irrigation techniques such as micro-sprinklers and drip systems, smart water management solutions, and water recycling methods. These approaches enhance water efficiency, minimize waste, and strengthen resilience in agricultural systems. Case studies illustrate the successful adoption of these technologies, underscoring their role in addressing climate change impacts. Climate adaptation strategies, such as drought-resistant crop varieties, bio-based filtration systems, and low-energy desalination, are also explored. Despite their potential, barriers such as high implementation costs, limited technical expertise, and institutional inefficiencies constrain widespread adoption. The study concludes by emphasizing the need for increased investment in water-saving technologies, capacity building, public-private partnerships, and policy reforms to advance water security and climate resilience.